Analisis Faktor-faktor yang Mempengaruhi Keberlanjutan Usaha Mikro Kecil dan Menengah (UMKM) yang Didirikan oleh Mahasiswa - Ainil Mardiah; Johni Eka Putra; Tio Devilishanti; Luthfi Nuraini; Muh. Aksa (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The purpose of this study is to analyze and determine the factors that influence the desire of MSMEs established by students. This research approach collects data through literature studies, which involve reading literature from various sources including books, journals and reports using qualitative and deductive approaches. The findings in this study are that there are two factors that influence MSMEs established by students, namely internal and external factors. Internal factors include managerial skills, innovation and creativity, and availability of capital. While external factors include access to markets, government policies, and market competition. In addition, there are strategies for the sustainability of MSMEs established by students, including improving management skills, developing solid business plans, increasing innovation and creativity, strong collaboration and networks, and sustainable growth of MSMEs.